2023
DOI: 10.1007/s43032-023-01253-5
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-210-3p Regulates Endometriotic Lesion Development by Targeting IGFBP3 in Baboons and Women with Endometriosis

Abstract: MicroRNAs (miRs) play an important role in the pathophysiology of endometriosis; however, the role of miR-210 in endometriosis remains unclear. This study explores the role of miR-210 and its targets, IGFBP3 and COL8A1, in ectopic lesion growth and development. Matched eutopic (EuE) and ectopic (EcE) endometrial samples were obtained for analysis from baboons and women with endometriosis. Immortalized human ectopic endometriotic epithelial cells (12Z cells) were utilized for functional assays. Endometriosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Inflammatory cytokines are increased in the peritoneal fluid of women with endometriosis [30], likely influencing gene expression. Indeed, miRNAs, 9 Notch signaling, aromatase enzymes, prostaglandins, and progestin responsiveness are altered in lesions compared to matched endometrial tissues [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines are increased in the peritoneal fluid of women with endometriosis [30], likely influencing gene expression. Indeed, miRNAs, 9 Notch signaling, aromatase enzymes, prostaglandins, and progestin responsiveness are altered in lesions compared to matched endometrial tissues [31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Further, patient rather than tissue type, that is lesion or endometrium, was the primary determinant of gene expression based on principal component and UMAP plots. The differences observed in macrophage gene expression are likely due to the presence of peritoneal and monocyte-derived macrophages in lesions, compared to tissue resident macrophages in the eutopic endometrium [4345].…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA has been shown to be downregulated in the ectopic endometrium of women and baboons with endometriosis, while IGFBP3 and COL8A1 expression was increased in the ectopic endometrial tissue. MiR-210 suppression was shown to contribute to endometriotic lesion development by increasing cell proliferation and migration [ 161 ].…”
Section: Role Of Micrornas In the Pathophysiology Of Endometriosismentioning
confidence: 99%
“…Compared to other RNA species, miRNAs are relatively RNAase-resistant, rendering them more stable against degradation ( 9 ). Recently research has expanded into elucidating miRNA profiles of endometriosis ( 10 12 ), and investigating how changes in miRNA expression may impact gene expression in ectopic endometrial tissue ( 13 , 14 ). While recent studies have reported promising results for the use of miRNA signatures in endometriosis diagnosis ( 15 19 ), gaps remain in our understanding of the relationship between miRNAs and endometriosis etiology ( 12 ).…”
Section: Introductionmentioning
confidence: 99%